Dictionary of environmental health - Spellman, Frank R. (Bernan Press, 2022)
"The Dictionary of Environmental Health is a one-of-a-kind comprehensive reference that serves as both a dictionary and encyclopedia. It defines over 17,000 words illustrating the enormous magnitude of the environmental health field. This book is an indispensable resource for individuals throughout environmental and public health industries"--